The Statistical effect of Financial Inclusion on economic growth-Dynamic panel data analysis during the period (2010-2021)- - Boutchous Nadjla; Chenikhar Abdelwahab (Journal of North African Economies, 2025)
This research paper aims to statistically study the impact of financial inclusion on economic growth in selected developed and developing countries according to the data availability over the period (2010- 2021). By constructing a multidimensional financial inclusion index, using SARMA methodology for each country and applying the dynamic panel regression model based on the system GMM for the short and long run regression. The results shows that financial inclusion index negatively and significantly influence economic growth in the short run regression in developed countries and positively influence economic growth in the long run regression. While it has a positive, significant impact on economic growth in the short run in developing countries and negative in long run. The findings reveals that the impact of financial inclusion on economic growth vary from country to other due to the variation of social and economic factors.